Organizational culture and career development in the British civil service. Issue 8 (16th November 2020) - Reeder, Neil
ABSTRACT: Quantitative analysis has rarely been used to assess the organizational culture of the British civil service. This paper matches a framework based on features of prominent theories against British Civil Service People Survey data for 2010–2018 for 71 organizations. The analysis shows a shift over that timescale to a culture giving significantly greater emphasis to personal development, with staff given more responsibility to achieve their organization's mission come what may.